A Catholic Moral Appraisal of In Vitro Gametogenesis - Pugeda, Teofilo Giovan S, III (Archīum Ateneo, 2022)
In vitro gametogenesis is the process of deriving gametes from embryonic stem cells or induced pluripotent stem cells. While not as well-known as in vitro fertilization; IVG could lead to more moral issues that would require corresponding responses from the Magisterium. Because IVG remains at the experimental stage; mainly using mice; the Magisterium has not issued any such responses in a document along the lines of Donum vitae and Dignitas personae. This essay situates IVG within Catholic moral teachings for those who are unfamiliar with the teachings of the Church but who are interested in forming their consciences and those of others on what is undoubtedly a peculiar medical technique with many moral ramifications.